Madīnat al-Zahrā', Spain. Conservation and Investigation of an Iron Gate. Research Carried Out between September 2020 and March 2021 - Ugolini Sánchez-Barroso, Alejandro (e-Forschungsberichte des DAI, 2023)
In 2019, iron elements of a gate were discovered at Madīnat al-Zahrā', an Islamic purpose-built capital city near Córdoba (Spain). The metal objects have subsequently been cleaned, restored and documented. The archaeological remains provide a unique opportunity to study the constructive details of a gate dating to the early 11th century CE.